IMPROVING THE ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) THROUGH DEVELOPING EFFECTIVE INTERPERSONAL COMMUNICATION AND TRANSFORMATIONAL LEADERSHIP - Herfina .; Dian Wulandari (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2019)
The teacher’s Organizational Citizenship Behaviour (OCB) become an important factor that involve in the teaching process at school. Unfortunately, based on the preliminary survey at several Junior High-School in Bogor, it had been found that many teachers had low-level of OCB. In addition, it had been found that teachers had ineffective interpersonal communication and had received less transformational leadership. Based on that issue, we formulated the objectives of this research as to improve the teachers’ OCB through developing effective interpersonal communication and transformational leadership. This research was carried out at 266 teachers from 20 Junior High-Schools, in Bogor.  This research was used correlational technique to assess the degree of relationship among those variables. The findings of this research can be summarized that there is a positive and significant correlation (1) between interpersonal communication with OCB (r=0.604, p0.01), (2) transformational leadership with OCB (r=0.602, p0.01), and between interpersonal communication and transformational leadership simultaneously with OCB (r=0.613, p0.01). These findings supported the recommendations to improve OCB through developing teachers’ interpersonal communication effectiveness and school principals’ transformational leadership.